(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Sediments samples from three dams and rivers in Zamfara State were analyzed for chemical association of the metals (Zn, Cd, Cr, Pb and Hg) using sequential extraction method to determine the amount of the heavy metals available for absorption. The concentrations were determined in four fractions. The concentration of heavy metals in the food crop (tomatoes) was also determined using atomic absorption spectrometry (AAS). The sequential extraction was carried out using (1.0 g) of powder sample weighed into a glass centrifuge (60 ml) and fractions were obtained. Comparing the way the metals were bound to the different fractions in the sediments, it showed clearly that the metals in the sediments are bound to different fractions with different strength. Cd and Cr were primarily in the carbonate bound fraction while Zn and Hg appear mainly in the residual phase. Pb was found in carbonate, exchangeable and water soluble fractions. The distribution of the five metals studied revealed their differences in mobility. From the five elements studied, Cd (14.739- 39.931%) and Pb (0.105- 9.832%) appeared to be the most readily solubilized, thus making these elements the most potentially bioavailable. This may present a real threat as Cd and Pb are transferred into the food chain from soil contaminated by these metals. Zn and Cr levels in the tomatoes, were within international standard while Cd (0.1022 mg/l), Pb (0.2104 mg/l) and Hg (1.8818 mg/l) levels were far above (0.01, 0.01 and 0.001mg/l) USEPA standard for drinking water. Two indices such as contamination